Could a new cross-listed method of article publication fuel growth of data from interdisciplinary research - Jason A. Aimone; Charles N. Noussair (Scientific Data)
Researchers may avoid taking on interdisciplinary projects due to concern that publications outside of their own field would not be rewarded in their home departments. This means that data with an interdisciplinary focus is underprovided. We propose that journal parent publishers facilitate “cross-listed” journal publications where papers can be submitted to and peer-reviewed simultaneously by two journals, in different fields, with joint publication under a single DOI.